Reciclagem de escória de forno panela de aciaria elétrica em material cerâmico - Cardoso, Marília Duarte (Universidade do Vale do Rio dos Sinos, 2009)
The slag is one of the many solid wastes generated in the steelmaking processes of steel production, which is constituted by metallic and non-metallic oxides. Depending on the process of slag generation, it can be slag blast furnace (smelting reduction of ores) or electric arc furnace (steel production). The slag ladle furnace from electric steelmaking, used in this study is generated in the stage of secondary refining in ladle furnace, which is the stage of refinement most used in Brazil. There are other solid wastes generated in the steel plant, such as electric arc furnace dust, refractory and plastics, which are sometimes in small quantities, and because of operational issues the company is unable to be segregated. The recycling of solid waste is a practice that should be incorporated as an alternative when there is no chance of minimizing. In recent years research on recycling of slag outside turned mainly to the incorporation in cement and concrete (as aggregate or filler kid-function) and more recently a few studies are related to its addition in the ceramic material. Actually, there is a worldwide trend to recycle solid waste in combination (more than one residue in the formation of a material) and very often this occurs in ceramic materials due to its high capacity to incorporate other materials. This research, with the various methods of characterization of the slag from ladle furnace, were carried out to evaluate the technical feasibility of recycling in ceramic material. Considering the conditions of this study and all tests (loss on ignition, thermal analysis, linear shrinkage, mechanical strength in bending, water absorption, porosity, visual analysis and microscope and SEM) used to study the ladle furnace slag, except the test of water absorption (specimens sintered at 950°C - D1 to D45 and 5% to 10%), the s lag has shown a potential to be used as by-product. The samples D45 showed a trend of greater strength than the bodies D1, this is probably related to the least amount of CaO to the slag contain D45, a characteristic linked to its longer storage. The results show the incorporation up to 15% (maximum level tested) of the ladle furnace from electric steelmaking in the ceramic material as bricks or structural blocks.
Keywords: Escória de forno panela; Reciclagem; Material cerâmico; Ladle furnace slag; Recycling; Ceramic material; ACCNPQ::Engenharias::Engenharia Civil